f(3√x-2)=9x+7√x 用配凑法求函数解析式!

来源:学生作业帮助网 编辑:作业帮 时间:2024/05/06 05:07:07

f(3√x-2)=9x+7√x 用配凑法求函数解析式!
f(3√x-2)=9x+7√x 用配凑法求函数解析式!

f(3√x-2)=9x+7√x 用配凑法求函数解析式!
设3√x-2=t≥-2
∴3√x=t+2,√x=(t+2)/3
∴x=(t+2)²/9
∴f(t)=f(3√x-2)=9x+7√x
=9*(t+2)²/9+7(t+2)/3
=t²+4t+4+7/3t+14/3
=t²+19/3*t+26/3
∴f(x)=x²+19/3*x+26/3 (x≥-2)

f(3√x-2)=[(3√x)²-12(√x)+4]+19√x-4
=[3√x-2]²+(19/3)[3√x-2]+(26/3)
=[3√2-x]²+(19/3)[3√x-2]+(26/3)
则:f(x)=x²+(19/3)x+(26/3),(x≥-2)

t=3√x-2,则x=(t+2)²/9
9x+7√x=(t+2)²+7(t+2)/3
f(t)=(t+2)²+7(t+2)/3
即f(x)=(x+2)²+7(x+2)/3

f(3√x-2)=9x+7√x =(3√x-2)平方+19/3(3√x-2)+26/3
所以f(x)=x平方+19/3x+26/3

f(3√x-2)=9x-12√x +4+5/3(3√x-2)-2/3=(3√x-2)²+5/3(3√x-2)-2/3
所以函数解析式为f(x)=x²+5/3x-2/3

法1:令t=3√x-2可得x=((t+2)/3)^2
将x带入得:f(t)=t^2+(19/3)t+26/3
法2:配凑法
由于9x+7√x =(3√x)^2+7√x=(3√x-2)^2+19√x-4=(3√x-2)^2+19/3(3√x-2)+26/3
所以f(3√x-2)=(3√x-2)^2+19/3(3√x-2)+26/3
即f(x)=x^2+(19/3)x+26/3